The salvation and transformation ministries, incorporated: a case study on a civic-oriented Christian organization - Aguila, Rafael Daniel M.
This research sought to find out more about the nature and functions of the Salvation and Transformation Ministries, Incorporated (STMI) -- a pseudonym, using the case study method. The organization presents itself as a unique one to study, as it is predominantly a religious group, and it tries to tackle a problem not willingly faced and accepted by society -- prostitution. Specifically, the group concentrates on bargirls of establishments along Timog Avenue. The research reveals that none of the prostitutes the STMI members have encountered have truly left the profession. Although the girls has shown signs of change, they inevitably regressed back. However, continuous reinforcement of relationships are being undertaken by the volunteers/ counselors. This paper primarily focuses on communication patterns and strategies employed by STMI members as they strive to achieve organizational objectives, principally to get the prostitutes out of the trade and second, to evangelize. The STMI is a young organization, and this fact lends more interest to the study. New methods, strategies and organizational activities are continually being experimented upon as the group is very receptive to change and evolution. Organizational hierarchy was found to be somewhat loose because of a lack of members. A generally informal intra-organizational set-up prevails. The success of the group is evaluated utilizing different criteria not withstanding its short history. Based from subjective evaluation, STMI's ability to achieve general organizational goals has been deemed to be severely limited.